Breastfeeding Practices Among Mothers of Children With Orofacial Clefts in an African Cohort. (August 2020) - Adekunle, Adegbayi Adeola; Adamson, Olawale; James, Olutayo; Ogunlewe, Omobolanle M.; Butali, Azeez; Adeyemo, Wasiu Lanre
Objective: To carry out a survey of breastfeeding practices and related challenges among mothers with orofacial cleft babies attending the cleft clinic of a tertiary health institution. Methodology: This was a cross-sectional descriptive study using an interviewer-administered questionnaire. Sample population was all mothers of babies aged between 1 and 18 months with nonsyndromic orofacial clefts attending the cleft clinic of a tertiary health institution in Nigeria. Result: A total of 65 mothers participated in the study. Initiation of breastfeeding was reported by the majority (83%, n = 54) of the mothers, and only 18.5% (n = 10) of this proportion continued exclusive breastfeeding. Inability of the babies to suck was reported by 46% (n = 30) of the mothers as being the most important challenge in breastfeeding. There was a significant correlation between the type of cleft and challenge in breastfeeding (Fisher exact P = .001). Sixty-three percent (n = 41) of the mothers reported they received no counseling on overcoming challenges associated with feeding their babies with a cleft at the facility where they delivered. Sixty-nine percent (n = 45) reported they first received nutritional information from the cleft clinic at presentation. The most adopted substitute for breastfeeding was the use of regular feeding bottles (n = 24, 43.6%). Conclusion: Rate of initiation of breastfeeding for children with orofacial clefts in this African cohort is higher than reported in other populations despite the low level of nutritional counseling of the mothers after delivery.